ANALISIS KINERJA PROFITABILITAS SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA SEBELUM DAN SAAT COVID-19 - Dwi Aprilariadi; Slamet Riyadi (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This research is a type of quantitative research with the aim of to test the impact of Covid-19 on the company's financial performance pharmacy listed on the Indonesia Stock Exchange. This sample was taken from pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) that can accessed through the website (www.idx.co.id). The population in this study were all pharmaceutical companies listed on the Indonesia Stock Exchange as many as 12 companies. The sample used in this study were 11 companies in the 2018-2021 period.The research method uses quantitative methods, the data used in this study is secondary data in the form of financial statements of pharmaceutical companies listed on the Indonesian stock exchange. Analysis of the data using a paired sample mean difference test Paired Sample Test using the SPSS application, and financial performance measurement using profitability ratios. Profitability ratios consist of Net Profit Margin, Rate of Return on Assets, and Return on Equity. The results showed that there was no significant difference to the financial performance of the profitability ratios of pharmaceutical companies listed on the IDX both before the Covid-19 pandemic and during the Covid-19 pandemic.